1976
DOI: 10.1126/science.819992
|View full text |Cite
|
Sign up to set email alerts
|

Visual Discrimination Impaired by Cutting Temporal Lobe Connections

Abstract: An attempt was made to transect the white matter that connects the anterior temporal lobe with dorsal and medial brain areas. Eight monkeys were trained preoperatively on a visual discrimination and tested postoperatively for retention and relearning of the task. They were also tested for Klüver-Bucy symptoms. The two animals that had complete lesions were unable to relearn the visual discrimination. It is suggested that human medial temporal lesions may produce their effects on learning and retention by damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

1978
1978
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 17 publications
1
18
1
Order By: Relevance
“…This dissociation resembles that reported by ZolaMorgan et al (1982), who found that lesions of the temporal stem disrupted visual pattern discrimination learning but not recognition memory, whereas combined ablations of the amygdala and hippocampus had the opposite effect. The available data suggest that the substrate for the acquisition of pattern discriminations includes the following temporal-lobe components: the posterior inferior temporal cortex (Cowey and Gross, 1970;Iwai and Mishkin, 1968), the white matter ofthe temporal stem (Horel and Misantone, 1976;Zola-Morgan et al, 1982) and temporal-lobe portions of the striatum (Buerger et al, 1974;Divac et al, 1967; and the present results). The evidence thus points to the existence of a corticostriatal pathway for pattern discrimination learning that is partially independent of the corticolimbic pathway for recognition memory (cf.…”
Section: Visual Pattern Discriminationssupporting
confidence: 58%
“…This dissociation resembles that reported by ZolaMorgan et al (1982), who found that lesions of the temporal stem disrupted visual pattern discrimination learning but not recognition memory, whereas combined ablations of the amygdala and hippocampus had the opposite effect. The available data suggest that the substrate for the acquisition of pattern discriminations includes the following temporal-lobe components: the posterior inferior temporal cortex (Cowey and Gross, 1970;Iwai and Mishkin, 1968), the white matter ofthe temporal stem (Horel and Misantone, 1976;Zola-Morgan et al, 1982) and temporal-lobe portions of the striatum (Buerger et al, 1974;Divac et al, 1967; and the present results). The evidence thus points to the existence of a corticostriatal pathway for pattern discrimination learning that is partially independent of the corticolimbic pathway for recognition memory (cf.…”
Section: Visual Pattern Discriminationssupporting
confidence: 58%
“…One (Douglas & Pribram, 1966) required monkeys to discriminate between two circles (diameters of 3 A versus Vi inch). Nevertheless, it is known that lesions of temporal white matter, including temporal stem, can impair visual discrimination performance (Horel & Misantone, 1976). In the other two positive studies the lesions were larger than those in the nine negative studies, and included damage to structures other than amygdala.…”
Section: Studies Of Monkeys With Amygdala Lesionsmentioning
confidence: 97%
“…Evidence of the second kind comes from two studies, which have assessed the behavioral effects of selective damage to temporal stem (Horel & Misantone, 1976;Zola-Morgan, Squire, & Miskin, 1982). In the first study lesions of the stem, without accompanying damage to hippocampus, severely impaired the ability of monkeys to relearn a preoperatively acquired visual discrimination, and the degree of impairment correlated with the extent of the lesion (Figure 6.18).…”
Section: The Temporal-stem Hypothesis: Relevant Datamentioning
confidence: 99%
“…The probe was "inserted into the hole about 12 to 15 mm and moved in a medial and lateral direction. The intention was to make a horizontal slit dorsal to the anterior temporal lobe, above the amygdala and laterally up to the insula" (215). In these cases, the extents of the lesions were plotted on representative coronal sections.…”
Section: Temporal Stem Hypothesis Revisitedmentioning
confidence: 99%